A multi-stimuli-responsive metallosupramolecular gel based on pillararene hierarchical assembly. Issue 5 (10th January 2023) - Li, Yong-Fu; Guan, Wen-Li; Wang, Chun-Yu; Wang, Yan; Lin, Qi; Yang, Ying-Wei
Abstract : A metallosupramolecular polymer network is constructed by hierarchical self-assembly of a double-armed pillar[5]arene, a ditopic guest, and zinc ions, where host-guest recognition and metal-ligand coordination interactions play a crucial role. Abstract : A metallosupramolecular polymer network (DSPy⊂SHP5@Zn) is constructed by the hierarchical self-assembly of a double-armed pillar[5]arene host (SHP5), a ditopic guest (DSPy), and Zn 2+ ions, in which host–guest recognition and metal–ligand coordination interactions play a crucial role. Owing to the reversible feature of both dynamic covalent and noncovalent interactions, the DSPy⊂SHP5@Zn assembly can form metallosupramolecular gels, which show good sol–gel transition properties in response to various external stimuli, including thermal, redox, and pH changes, and competitive guests. Interestingly, the DSPy⊂SHP5@Zn assembly can serve as an excellent sensor for highly selective dual-channel recognition of OH̄, and therefore a convenient and feasible test kit for sensing OH̄ anions based on DSPy⊂SHP5@Zn is fabricated. The present work provides a facile and efficient method to construct multi-stimuli-responsive smart gels, which may further enrich and expand the scope and application of smart supramolecular materials.